Synthesis of N-Substituted 3-Chloro- 2-azetidinones for 2, 4-diamino-6- hydroxy pyrimidin (Journal of the College of Basic Education, 2023)
This search involved synthesis of several new N-Substituted -3-chloro-2-azetidinones which were known as a high medicinal effectiveness for 2,4-Diamino-6-hydroxy pyrimidin in two steps. The first step includedpreparation Shiff bases (1-6) by condensation of 2, 4-Diamino-6-hydroxypyrimidin with many substituted aldehydes(4-hydroxy benzaldehyde, 2-bromobenzaldehyde, 4-dimethyl amino benzaldehyde, = 4-nitrobenzaldehyde, salicylaldehyde, 4-chlorobenzaldehyde), then the secondstep included, preparation new six azetidinones compounds (7-12) byreaction of chloroacetylchloride with the prepared Schiff bases in the firststep in the presence of triethylamine. The structures of synthesizedcompounds were- characterized by physical properties (FT-IR, UV andsome of them by 'H-NMR, C_NMR spectroscopy) were recorded.